Analysis of psychological disorders in some characters of «El Nazareno» and «La fiesta de San Simón Garabatillo» - Villanueva Anderson, Nicolás Gustavo (2019)
The article will analyze some characters of «El Nazareno» and «La fiesta de San Simón Garabatillo» from a psychological point of view, because in these traditions Ricardo Palma’s characters show different attitudes or behaviors that reveal signs of possible psychological disorders currently. On the other hand, we seek to understand how the traditionalist, through his writing, was able to capture almost perfectly the characteristics of such disorders, as we start from the hypothesis that the Beggar Librarian had a poor knowledge of them, due to the non-existence of the science of Psychology at that time.